Anti-Foulant Ultrafiltration Polymer Composite Membranes Incorporated with Composite Activated Carbon/Chitosan and Activated Carbon/Thiolated Chitosan with Enhanced Hydrophilicity - Syeda Samia Nayab (MDPI AG, 2021)
A rapid increase in population worldwide is giving rise to the severe problem of safe drinking water availability, necessitating the search for solutions that are effective and economical. For this purpose, membrane technology has shown a lot of promise but faces the challenge of fouling, leading to a reduction in its lifetime. In this study, ultrafiltration polyethersulfone membranes were synthesized in two different concentrations, 16% wt. and 20% wt., using the phase inversion method. Chitosan and activated carbon were incorporated as individual fillers and then as composites in both the concentrations. A novel thiolated chitosan/activated carbon composite was introduced into a polyethersulfone membrane matrix. The membranes were then analyzed using Attenuated Total Reflection–Fourier-Transform Infrared spectroscopy(ATR-FTIR), Scanning Electron Microscopy (SEM), optical profilometry, gravimetric analysis, water retention, mechanical testing and contact angle. For membranes with the novel thiolated chitosan/activated carbon composite, Scanning Electron Microscopy micrographs showed better channels, indicating a better permeability possibility, reiterated by the flux rate results. The flux rate and bovine serum albumin flux were also assessed, and the results showed an increase from 105 L/m2h to 114 L/m2h for water flux and the antifouling determined by bovine serum albumin flux increased from 23 L/m2h to 51 L/m2h. The increase in values of water uptake from 22.84% to 76.5% and decrease in contact angle from 64.5 to 55.7 showed a significant increase in the hydrophilic character of the membrane.